Consumption of Chinese goods in southwestern Europe: a multi-relational database and the vicarious consumption theory as alternative model to the industrious revolution (eighteenth century). Issue 1 (2nd January 2019) - Perez-Garcia, Manuel
Abstract: This article discusses the application of new technologies, software coding and computer analysis in the social sciences and humanities, mainly in the field of economic history. In the last two decades, the use of new computer technologies among historians to develop theories and solve questions has fostered a vibrant historiographical debate. However, these new digital tools have largely been used as an end in themselves, rather than as a means to develop hypotheses and answer questions. This has prevented researchers from fully exploiting such technologies in their field. In this article, I discuss how I designed a new multi-relational database using the "Access" package and SQL language to test the "industrious revolution" hypothesis and present the "vicarious consumption" theory as an alternative model for analyzing the eighteenth-century circulation of Chinese goods in the Western Mediterranean region. It presents the cross-referencing method I used to analyze the historical information I collected, mainly from probate inventories and trade records. This method makes it possible to navigate through the data in a way that goes beyond the traditional use of "excel" tables.